Pengaruh Media Digital terhadap Minat Belajar Siswa di SMA Swasta Budisatrya - Zahra Nabila Iqbal; Muhammad Wafi Siregar; Abdul Fattah Nasution (Lembag, 2025)
The development of digital technology has brought changes to the learning process in schools, so that the use of digital media has become one of the efforts to increase students' interest in learning. This study aims to determine the effect of digital media on students' interest in learning at Budisatrya Private High School. This study uses a quantitative approach with a survey method. The research subjects were 10th grade students at Budisatrya Private High School with a total of 32 respondents. The research instrument was a Likert scale questionnaire consisting of 9 statements for the digital media variable and 7 statements for the student learning interest variable. Data analysis techniques included validity testing, reliability testing, normality testing, and simple linear regression analysis. The results showed that all statement items were valid and reliable. Normality testing showed that the data was normally distributed. The regression analysis results showed a significance value of 0.003, which is less than 0.05, so it can be concluded that digital media has a significant effect on student learning interest at Budisatrya Private High School. This study is expected to be a consideration for teachers and schools in optimizing the use of digital media in the learning process.